Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

New role for penicillin acylases: degradation of acyl homoserine lactone quorum sensing signals by Kluyvera citrophila penicillin G acylase - Mukherji, Ruchira; Varshney, Nishant Kumar; Panigrahi, Priyabrata; Suresh, C. G.; Prabhune, Asmita (Enzyme and Microbial Technology, 2014)
Use of penicillin acylases for the production of semi-synthetic penicillins is well-known. Escherichia coli penicillin G acylase (EcPGA) has been extensively used for this purpose; however, Kluyvera citrophila penicillin G acylase (KcPGA) is assumed to be a better substitute, owing to its increased resilience to extreme pH conditions and ease of immobilization. In the present article we report a new dimension for the amidase activity of KcPGA by demonstrating its ability to cleave bacterial quorum sensing signal molecules, acyl homoserine lactones (AHL) with acyl chain length of 6-8 with or without oxo-substitution at third carbon position. Initial evidence of AHL degrading capability of KcPGA was obtained using CV026 based bioassay method. Kinetic studies performed at pH 8.0 and 50 degrees C revealed 3-oxo-C6 HSL to be the best substrate for the enzyme with V-max and K-m values of 21.37+0.85 mM/h/mg of protein and 0.1+0.01 mM, respectively. C6 HSL was found to be the second best substrate with V-max. and K-m value of 10.06+0.27 mM/h/mg of protein and 0.28+0.02 mM, respectively. Molecular modeling and docking studies performed on the active site of the enzyme support these findings by showing the fitting of AHLs perfectly within the hydrophobic pocket of the enzyme active site. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acyl homoserine lactones; CV026; KcPGA; Quorum quenching

Possible correlation between bile salt hydrolysis and ahl deamidation: staphylococcus epidermidis RM1, a potent quorum quencher and bile salt hydrolase producer - Mukherji, Ruchira; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2015)
The aim of the present work was to isolate a bile salt hydrolase (BSH) producer from fermented soy curd and explore the ability of the BSH produced to cleave bacterial quorum sensing signals. Bacterial isolates with possible ability to deconjugate bile salts were enriched and isolated on De Man, Rogosa and Sharpe (MRS) medium containing 0.2 % bile salts. BSH-producing positive isolate with orange-pink-pigmented colonies was isolated and was identified as a strain of Staphylococcus epidermidis using biochemical and phylogenetic tools. S. epidermidis RM1 was shown to possess both potent BSH and N-acyl homoserine lactone (AHL) cleavage activity. Genetic basis of this dual-enzyme activity was explored by means of specific primers designed using S. epidermidis ATCC 12228 genome as template. It was observed that a single enzyme was not responsible for both the activity. Two different genetic elements corresponding to each of the enzymatic activity were successfully amplified from the genomic DNA of the isolate.
Keywords: AHL acylase; Bile salt hydrolase; CV026; Quorum quenching; Staphylococcus epidermidis